2016
DOI: 10.1158/1535-7163.mct-15-0488
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Myeloma Cell Death via Novel Intracellular Activation of Caspase-10–Dependent Apoptosis by Carfilzomib and Selinexor

Abstract: Exportin1 (XPO1; also known as chromosome maintenance region 1, or CRM1) controls nucleo-cytoplasmic transport of most tumor suppressors and is overexpressed in many cancers, including multiple myeloma, functionally impairing tumor suppressive function via target mislocalization. Selective inhibitor of nuclear export (SINE) compounds block XPO1-mediated nuclear escape by disrupting cargo protein binding, leading to retention of tumor suppressors, induction of cancer cell death, and sensitization to other drugs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…These include the oral PI oprozomib 103 that is related to carfilzomib and marizomib 104 ; dinaciclib, 105 an oral cyclin-dependent kinase inhibitor; selinexor, 106 a selective inhibitor of exportin 1; venetoclax, 107 a selective inhibitor of bcl-2, and isatuximab, 108 a novel MAb that also targets CD38 and may have a more favorable pharmacological profile than does daratumumab. Other agents in early clinical trials include immune checkpoint inhibitors (pembrolizumab and nivolumab) and chimeric antigen receptor T cells.…”
Section: Drugs Approved For Therapy For Multiple Myelomamentioning
confidence: 99%
“…These include the oral PI oprozomib 103 that is related to carfilzomib and marizomib 104 ; dinaciclib, 105 an oral cyclin-dependent kinase inhibitor; selinexor, 106 a selective inhibitor of exportin 1; venetoclax, 107 a selective inhibitor of bcl-2, and isatuximab, 108 a novel MAb that also targets CD38 and may have a more favorable pharmacological profile than does daratumumab. Other agents in early clinical trials include immune checkpoint inhibitors (pembrolizumab and nivolumab) and chimeric antigen receptor T cells.…”
Section: Drugs Approved For Therapy For Multiple Myelomamentioning
confidence: 99%
“…Preclinical studies have provided a rationale for combining selinexor with PIs (Kashyap et al , ; Nair et al , ; Rosebeck et al , ; Turner et al , ). The addition of selinexor to a PI has a synergistic effect on cell death of myeloma cell lines and primary plasma cells derived from patients with RRMM, and the combination demonstrated greater antimyeloma activity in a murine xenograft model than either agent alone (Kashyap et al , ; Rosebeck et al , ; Turner et al , ).…”
mentioning
confidence: 99%
“…Preclinical studies have provided a rationale for combining selinexor with PIs (Kashyap et al , ; Nair et al , ; Rosebeck et al , ; Turner et al , ). The addition of selinexor to a PI has a synergistic effect on cell death of myeloma cell lines and primary plasma cells derived from patients with RRMM, and the combination demonstrated greater antimyeloma activity in a murine xenograft model than either agent alone (Kashyap et al , ; Rosebeck et al , ; Turner et al , ). Selinexor‐PI combinations were associated with inhibition of BCL2 expression, increased cleavage and inactivation of AKT, activation of caspase‐10 and other caspases, and increased levels of IκBα and IκBα‐NFκB complexes, leading to neutralization of NF‐κB (Kashyap et al , ; Rosebeck et al , ; Turner et al , ).…”
mentioning
confidence: 99%
“…Interesting, this study found that SINEs suppressed the expression of cell division cycle 25 homolog A, bromodomain-containing protein 4 (BRD4) and c-Myc [49] . Moreover, combined treatment with selinexor and carfilzomib caused significant apoptosis of myeloma cells and primary plasma cells derived from relapsing/refractory myeloma patients [50] . The combination of selinexor and doxorubicin was highly effective against acquired drug resistance in ex vivo samples obtained from patients with either relapsed or refractory myeloma as well as in vivo xenograft models of myeloma.…”
Section: Role Of Selective Inhibitors Of Nuclear Export (Xpo1 Inhibitmentioning
confidence: 99%